REKAYASA PERBAIKAN PROSES PRODUKSI BONEKA DENGAN INTEGRASI METODE LINE BALANCING DAN VALUE STREAM MAPPING - Fut Tri Budi Ayu (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
Pradamas Toys is a small and medium industrial company in producing dolls with yelvo fabric base material. The purpose of this study is to know the waste in the puppet production process at Pradamas Toys and to propose improvement of production process to minimize waste and improve production process efficiency in Pradamas Toys. This research uses lean approach with value stream mapping (VSM) tools, at the beginning of the research done depiction of current state mapping on Pradamas Toys, after that do problem analysis using line balancing to leveling cycle time, fishbone diagram used to know factors causing production problem puppets and waste identification in each production process, then analyzed 5 Why and 5W1H to give suggestions for improvement of production process at Pradamar Toys. At current state mapping the production process time is 18.6032 minutes with a lead time of 9 days. After doing the calculation and equalization cycle time by using line balancing, then got the proposed future state mapping for doll production with process time of 14,7300 minutes and lead time of 5 days.